Identification of resistant sources in Durum wheat to Hessian fly (Diptera: Cecidomyiidae) - Boulamtat, Rachid; Kabbaj, Hafssa; Jaber, Hassna; Zaazoui, Nouhaila; Fikraoui, Nabil; Boutoumit, Soilam; Bassi, Filippo (2024)
Hessian fly (Mayetiola destructor) is the major pest in cereal areas and can cause up to 32 % yield losses on durum wheat (Lhaloui et al. 1992). Host plant resistance is a very effective approach for controlling this insect. Hessian fly (HF) has many biotypes, so far more than 37 HF resistance genes are deployed and incorporated into wheat varieties (Tang et al; 2018) to minimize the negative impacts of the pest. Some resistance genes were found ineffective due to appearance of new biotypes in HF population that break resistance genes in some countries (e.g. Morocco) (El Bouhssini et al. 2009). The main objective of the work is to identify new sources of resistance in durum wheat.